2023
DOI: 10.59292/bulletinbiomath.2023008
|View full text |Cite
|
Sign up to set email alerts
|

A compartmental fractional-order mobbing model and the determination of its parameters

Engin Işık,
Bahatdin Daşbaşı

Abstract: In this study, a mathematical model is presented with fractional-order differential equations in the Caputo sense that examines the time-dependent changes of variables representing individuals who are exposed to mobbing, individuals who are not exposed to mobbing, or individuals who gained resistance to mobbing, and individuals who practice mobbing. Existence and uniqueness, and boundedness and non-negativity of the solutions of the proposed model are examined. Additionally, the data set containing the time-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In fact, this new definition is an extension of the traditional derivative of a function. We have observed that fractional derivative becomes an important part of scientific world and is mainly used in the field of health such as the growth of COVID-19 [7,8], powerlaw modeling of coronavirus [9], modeling coronavirus disease [10], the Ebola epidemic disease [11], the hantavirus of the European moles [12], and in some mathematical models [13][14][15][16][17]. For more information about conformable derivatives, we advise the readers to look at the works [18][19][20] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this new definition is an extension of the traditional derivative of a function. We have observed that fractional derivative becomes an important part of scientific world and is mainly used in the field of health such as the growth of COVID-19 [7,8], powerlaw modeling of coronavirus [9], modeling coronavirus disease [10], the Ebola epidemic disease [11], the hantavirus of the European moles [12], and in some mathematical models [13][14][15][16][17]. For more information about conformable derivatives, we advise the readers to look at the works [18][19][20] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of semi-analytical method and integral transforms is an important tool for solving FDEs. Several integral transforms like Laplace and Sumudu transform combined with different fractional operator like Caputo [13][14][15][16][17][18][19][20], Caputo Fabrizio [21,22], and ABC [23,24] to solve FDE. Literature consists of different methods like fractional homotopy perturbation transform method (FHPTM) [11], q-homotopy analysis method [25], Sumudu residual power series method [26], and operational matrix method [27][28][29] that are used to solve fractional order Bloch equation.…”
Section: Introductionmentioning
confidence: 99%